Social construction and the logic of money : financial predominance and international economic leadership - Barkin, J. Samuel, 1965- (SUNY series in global politics., 2003)
While other studies of international leadership have looked at a variety of measures to predict behavior, this book demonstrates that the key factor is international finance. J. Samuel Barkin uses an innovative blend of rationalist and constructivist methodologies, approaches to international political economy that normally exist in isolation from one another. Barkin argues that the level of a country's involvement in international finance specifically motivates it to lead. This is particularly relevant today, given the on-going discussions on how to respond to local and global financial crises. Barkin illustrates his theory with an episodic history of international monetary leadership over the last four centuries: Dutch leadership in the seventeenth century; British leadership in the nineteenth; the failure of leadership in the interwar era and Great Depression; and the role of the U.S. in the construction of an international economic infrastructure since World War II.